Holistic Management of A 10 Year Old Boy Patient with Scabies Through A Family Medicine Approach - Atthariq, Muhammad Naufal; Musliha, Hany (Jurnal Penelitian Perawat Profesional, 2025)
Scabies, also known as gudik or buduk, is a highly contagious disease, particularly in communities where individuals live in close quarters. Population density in a residence is a significant risk factor, as it increases close physical contact and facilitates disease transmission. This study aims to identify risk factors and clinical issues in patients while applying the principles of family medicine to provide holistic and comprehensive management using a patient-centered and family-oriented approach based on Evidence-Based Medicine. This study is a case report. Primary data were collected through autoanamnesis, alloanamnesis, physical examination, and home visits to gather information on family, psychosocial, and environmental factors. The assessment was conducted holistically, covering the initial phase, process, and conclusion of the study through both quantitative and qualitative approaches. The patient presented with complaints of reddish spots on the hands and feet, accompanied by itching that had persisted for approximately two weeks. Diagnosis and treatment were carried out in accordance with theoretical guidelines and relevant research. Following the intervention, there was a reduction in clinical symptoms and an improvement in the knowledge of both the patient and their family. Holistic management plays a crucial role in enhancing patients' knowledge, attitudes, and behaviors regarding their illness. Additionally, family involvement is essential in supporting the patient's treatment and recovery.